John C. Robinson letter to Thomas H. Kent regarding Iowa Bird Life printing errors with his bird sightings, January 1, 1983 - Robinson, John C., 1959-et al (1983)
Letter from John C. Robinson to Thomas H. Kent regarding Iowa Bird Life printing errors with his bird sightings, January 1, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed